Representations of Femininity in Contemporary South Korean Women's Literature. - Elfving-Hwang, Joanna (BRILL, 2010)
This book discusses perceptions of 'femininity' in contemporary South Korea and the extent to which fictional representations in South Korean women's fiction of the 1990s challenges the enduring association of the feminine with domesticity, docility and passivity.